2003
DOI: 10.1292/jvms.65.1325
|View full text |Cite
|
Sign up to set email alerts
|

CD38 Gene Disruption Inhibits the Contraction Induced by .ALPHA.-Adrenoceptor Stimulation in Mouse Aorta

Abstract: ABSTRACT. CD38 is an ectoenzyme with ADP-ribosyl cyclase and hydrolase activities, which synthesizes cyclic ADP-ribose from NAD and hydrolyzes cyclic ADP-ribose to ADP-ribose. It has been shown that cyclic ADP-ribose is a potent Ca 2+ mobilizing messenger in many cells. To know the physiological role of cyclic ADP-ribose in vascular smooth muscle, we examined the effects of various agonists in the aorta isolated from CD38 knockout (CD38 -/-) mouse. Western blot analysis showed that CD38 protein was detected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 28 publications
(24 reference statements)
0
16
0
Order By: Relevance
“…The previously reported literature has suggested that ADPR cyclase contributes to agonistinduced vasoconstriction. ADPR cyclase, cADPR, and RyRs participate in ANG II-mediated increases in [Ca 2ϩ ] i in preglomerular resistance arterioles (19); those triggered by KClinduced depolarization (17) and constrictor responses to NE are attenuated in aortic rings of CD38Ϫ/Ϫ mice (39). RyRs also have been implicated in NE signaling in vascular myocytes (8).…”
Section: Discussionmentioning
confidence: 99%
“…The previously reported literature has suggested that ADPR cyclase contributes to agonistinduced vasoconstriction. ADPR cyclase, cADPR, and RyRs participate in ANG II-mediated increases in [Ca 2ϩ ] i in preglomerular resistance arterioles (19); those triggered by KClinduced depolarization (17) and constrictor responses to NE are attenuated in aortic rings of CD38Ϫ/Ϫ mice (39). RyRs also have been implicated in NE signaling in vascular myocytes (8).…”
Section: Discussionmentioning
confidence: 99%
“…The mice also manifest multiple defects relating to Ca 2+ signaling, including that of insulin secretion [97], hormonal signaling in pancreatic acinar cells [98], migration of dendritic cell precursors [99], bone resorption [100], airway responsiveness [101], α-adrenoceptor signaling in aorta [102], cardiac hypertrophy [103], susceptibility to bacterial infection [55], as well as social behavior in mice through modulation of oxytocin secretion [66]. In humans, the deletion of the CD38 gene may well be lethal since no CD38-negative individual has yet been identified in a large screen [104].…”
Section: Enzymatic Synthesis Of Cadpr By Cd38mentioning
confidence: 99%
“…CD38-generated cADPR plays a critical role in Ca 2ϩ -induced insulin secretion (21), osteoclast-mediated bone resorption (35), vasoconstriction (27), myometrium function (9), and immune function (28,29). Using these mice, we have previously demonstrated that CD38 is the main source of cADPR in the lungs.…”
mentioning
confidence: 99%